Developing Interactive Multimedia-Based Locomotor Basic Motion Teaching Materials in the Physical Education Course - Fajar Sidik Siregar; Arifin Siregar; Ramlan Sahputera Sagala; Andi Nur Abady; Eva Faridah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This developmental research aims to produce products in the form of interactive multimedia when learning Physical Education in the PGSD FIP UNIMED Study Program, which is suitable for use as a learning resource. This type of research is research and development (Research and Development). The participants of this study consisted of 28 students enrolled in the PGSD physical education course. The designed product consists of interactive multimedia-based instructional material applications and videos demonstrating basic locomotor movements. The learning application includes fundamental locomotor motion materials such as walking, running, leaping, and other instructions that facilitate the basic locomotor motion process. The practicality of interactive multimedia is supported by the assessment findings conducted by media experts, which achieved a score of 4.84 (in the very good category), and material experts, who achieved a score of 4.83 (also in the very excellent category). These are interactive multimedia products specifically designed and evaluated for students enrolled in the PGSD study programme, focusing on physical education courses. The small-scale testing yielded a result of 85.95% in the "very good" category, while the large-scale tests achieved a value of 93.65% in the same category. The field implementation tests have demonstrated that the product is highly effective in facilitating interactive multimedia learning in Physical Education within the PGSD FIP UNIMED Study Programme. Therefore, it is deemed suitable for use as a learning resource.